Regionalne instrumenty wspomagania przedsiębiorczości (na przykładzie województwa podkarpackiego) - Strojny, Janusz (Regional Instruments of Supporting Entrepreneurship on the Example of Podkarpackie Voivodeship, 2006)
The article presents theoretical aspects of entrepreneurship functioning in the changing market. The subjects of considerations in the empirical part of the article are chosen instruments of entrepreneurship activisation on the territory of Podkarpackie province.The author attempts to stimulate entrepreneurship in the area of administration and social surrounding.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 621-629